(untitled) (Bangladesh Critical Care Journal, 2020)
Darier’s disease, also known as keratosis follicularis is a rare autosomal dominant inherited genodermatosis characterized by abnormal keratinization . A 39-year old non-diabetic, normotensive man presented to dermatology OPD with discretely distributed dark brown greasy, warty, malodorous, hyperkeratotic papules over his whole body for last 15 years. He has two young daughters and both has started initial stage of similar lesions for last 6 months. Characteristic v-shaped nicking at the tip of the nails with longitudinal red & white ridges were seen. Nails at the distal ends were broken. Biopsy of skin for histopathological examination showed more specific and confirmatory ‘corps ronds and grains’. This article reports a case of familial darier’s disease. Good improvement was noticed after acitretin therapy. Bangladesh Crit Care J March 2020; 8(1): 55-57